Diversity of Algae in Relation to Water Pollution of Satri Tank Chhatarpur (M.P.) India - Khare, Pushpendra Kumar (Ecoprint: An International Journal of Ecology, 2009)
This paper is report of phytoplankton from Satri Tank of Bundelkhand region, India. Total 43 species and 27 genera have been identified from Satri Tank, among these 18 species belonged to Chlorophyceae 17 species to Cyanophyceae, 6 to Bacillariophyceae and 2 to Euglenophyceae. Qualitatively Chlorophyceae were abundant. The species of Spirulina, Oscillatoria, Microcystics and Nostoc were dominant. The tank is indicative of highly eutrophic status and biologically dead in term of its unability to provide the aesthetic pleasure of swimming, boating and fishing. Key words: Lower plant; Phytoplankton; Eutrophic doi: 10.3126/eco.v13i0.1634 Ecoprint (An International Journal of Ecology) Vol. 13, 2006 Page:69-72